Implementation of Communicative Arabic Language Skills Based on TBL (Technology- Based Learning) for Students of Mti Tanjung Barulak and Ppti Malalo Tanah Datar - Devy Aiysah; Nurlaila Nurlaila; Akhyar Hanif; Kamaluddin Kamaluddin; Amelia Amelia; Nurul Aisyah (Yayasan Adra Karima Hubbi, 2026)
The low communicative Arabic speaking skills of madrasah and Islamic boarding school students remain a major challenge due to the dominance of grammar-oriented instruction, particularly nahwu and sharaf, and the limited availability of contextual oral practice. This condition was also identified among students of MTI Tanjung Barulak and PPTI Malalo, Tanah Datar Regency, who experienced difficulties in expressing ideas orally in Arabic. This study employed a descriptive evaluative design within a community service-based research framework to implement and assess a Technology-Based Learning intervention for improving students’ communicative Arabic speaking skills. The intervention was carried out through structured mentoring, guided training, interactive conversation exercises, audio-visual learning, dialogue simulations, and simple digital content production. The program was implemented in two stages: face-to-face activities and intensive mentoring. The participants consisted of 50 students from both institutions. The findings indicated observable improvements in students’ confidence, fluency, active participation, and motivation in Arabic speaking activities. Teachers and students perceived the TBL approach as more relevant, engaging, and contextual than conventional methods because it provided students with more meaningful opportunities to practice Arabic communication. The integration of technology with communicative learning also supported the creation of a more interactive learning environment. The study concludes that TBL-based communicative Arabic learning has the potential to strengthen students’ maharah al-kalam and may serve as an alternative instructional model for similar madrasah and Islamic boarding school contexts.